2022
DOI: 10.1007/s00267-021-01585-5
|View full text |Cite
|
Sign up to set email alerts
|

Making a Difference: Planning for Engaged Participation in Environmental Research

Abstract: Despite the rapid and accelerating rate of global environmental changes, too often research that has the potential to inform more sustainable futures remains disconnected from the context in which it could be used. Though transdisciplinary approaches (TDA) are known to overcome this disconnect, institutional barriers frequently prevent their deployment. Here we use insights from a qualitative comparative analysis of five case studies to develop a process for helping researchers and funders conceptualize and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 85 publications
(122 reference statements)
1
9
0
Order By: Relevance
“…While there are many ways to assess research impact outcomes (Ferguson et al, 2022;Kostoff, 1994), we find our project realised this impact in four key dimensions: magnitude, intensity, scope and duration. While most studies focus on one or two impact dimensions, we evaluate and offer evidence of impact realisation over all four dimensions.…”
Section: Realising Research Impact Outcomesmentioning
confidence: 94%
See 1 more Smart Citation
“…While there are many ways to assess research impact outcomes (Ferguson et al, 2022;Kostoff, 1994), we find our project realised this impact in four key dimensions: magnitude, intensity, scope and duration. While most studies focus on one or two impact dimensions, we evaluate and offer evidence of impact realisation over all four dimensions.…”
Section: Realising Research Impact Outcomesmentioning
confidence: 94%
“…Organisations measure impact intensity – the level of institutional effort in an intervention (Ferguson et al , 2022) – by assessing changes in organisational structures and the level of employee engagement within those structures. Participants in the follow-up focus group revealed that the intervention’s activities helped bring together cross-functional teams that offered diverse perspectives on developing effective technology solutions for clients (Capability 1).…”
Section: Realising Research Impact Outcomesmentioning
confidence: 99%
“…Conservation objectives are achieved through partnerships with public and private landowners. For our engagement process, we leveraged preexisting, mature 10‐year partnerships (Ferguson et al., 2022) with decision makers, resource managers, and boundary spanners (definitions and stakeholders in Appendices S2 & S3) across water management, planning, and conservation sectors. Engagement occurred over 6 years in several steps (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Three often-cited elements influence outcomes-impact: salience, the relevance of the information provided; legitimacy, the perception that the process is respectful and fair; and credibility, the trust in the technical results (Cash et al, 2003). Frequent, 2-way interactions among equal partners help achieve these elements, especially if mature preexisting relationships are present (Ferguson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our approach differs somewhat from other efforts to identify conservation questions and information needs (c.f., Ahlering et al, 2020;Sutherland et al, 2009Sutherland et al, , 2006 in that we first focused on analyzing existing reports, management plans, and peer-reviewed literature rather than soliciting information directly from resource managers. We employed this alternative approach to avoid overtaxing resource managers (Dilling & Berggren, 2015), and this is important when balancing considerations for when, how, and to what extent to involve stakeholders in the scientific process (Ferguson et al, 2022;Wilmer et al, 2021). However, as we found with tribal nations, underserved and overburdened communities may have fewer reports and less documentation available for this type of analysis, and so this approach should be used in addition to, and not a stand-in for, ethical consultation and collaboration.…”
Section: Benefits and Limitations Of Methodologymentioning
confidence: 99%